Comments on the new guidelines (2016) of the European Society of Cardiology (ESC) on prevention of cardiovascular disease Kommentar zu den neuen Leitlinien (2016) der Europäischen Gesellschaft für Kardiologie (ESC) zur kardiovaskulären Prävention - Hambrecht, R.; Albus, C.; Halle, M.; Landmesser, U.; Löllgen, H.; Schuler, G. C.; Perings, S. (Der Kardiologe, 2017)
The new European guidelines on prevention of cardiovascular diseases for the first time include both individualized interventions and population-based approaches. For individual risk assessment the SCORE charts are recommended and risk modifiers are introduced, such as socioeconomic status and family history of premature cardiovascular disease, with which the risk assessment can be reclassified. A treat to target strategy is recommended for management of dyslipidemia with a low-density lipoprotein (LDL) cholesterol target of <1.8 mmol/l (<70 mg/dl) or a reduction of at least 50% if the baseline is between 1.8 and 3.5 mmol/l (70 and 135 mg/dl) in patients at very high risk. The guidelines emphasize that there is an unmet need to reduce the prevalence of smoking, physical inactivity and obesity. Individual as well as population-based activities are needed to reduce these cardiovascular risk factors, including stronger laws and policies in public life, business and the media. It is emphasized that long-term and interdisciplinary preventive strategies are crucial to achieve and maintain life style changes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dyslipidemia; Individualization; Population-based approaches; Risk assessment; Risk factors